INDIGENOUS EXPERIENCES PRESERVED IN JHUMPA LAHIRI’S UNACCUSTOMED EARTH - Antony, Steffy (International Journal of Psychosocial Rehabilitation, 2020)
Unaccustomed Earth by Jhumpa Lahiri poignantly depicts the immigrant experiences of the Bengalis in diaspora. The author was herself an immigrant who lived in America and was raised by a Bengali family that often-visited India. Her personal level observation and experience of immigrant life can be examined in this collection of short stories. She has highlighted the themes of exile, cultural translation, alienation, identity crisis and rootlessness in Unaccustomed Earth. The characters in it are emotionally entangled in the diasporic spirit. Lahiri focusses on the first- and second-generation Indian Americans who are in the quest of their self in spite of the alienation and assimilation. This paper intends to dwell upon how the first-generation immigrants preserve their cultural traditions in a foreign land in Lahiri’s Unaccustomed Earth